2018
DOI: 10.3389/fpls.2018.00833
|View full text |Cite
|
Sign up to set email alerts
|

Cis-Effects Condition the Induction of a Major Unfolded Protein Response Factor, ZmbZIP60, in Response to Heat Stress in Maize

Abstract: Adverse environmental conditions such as heat and salt stress create endoplasmic reticulum (ER) stress in maize and set off the unfolded protein response (UPR). A key feature of the UPR is the upregulation of ZmbZIP60 and the splicing of its messenger RNA. We conducted an association analysis of a recombinant inbred line (RIL) derived from a cross of a tropical founder line, CML52 with a standard temperate line, B73. We found a major QTL conditioning heat-induced ZmbZIP60 expression located cis to the gene. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…a The tobacco root transformed with plasmid pBI121; b The tobacco root transformed with plasmid p1200::GUS; c The tobacco root transformed with plasmid p900::GUS; d The tobacco root transformed with plasmid p600::GUS; e The tobacco root transformed with plasmid p400::GUS; f The tobacco root transformed with plasmid pBI101; g The wild tobacco root showed that the upstream of the promoter sequence contained many core elements such as TATA-box (− 30 bp) and CAAT-box (− 96 bp), and the distance from TATA-box or CAAT-box to TSS was consistent with that of the results described in the previous studies in other plant promoters [29]. Besides the core components TATA-box and CAAT-box, the EcGS1b-P also had rootspecific function motif and cis-acting elements that were regulated by light, heat, hormones and temperature, which was also consistent with the previous studies [54][55][56][57]. It is worth to note that GS1b promoter contained root-specific expression element ROOT-MOTIFTAPOX, which indicated EcGS1b might be a root-preferential expression gene.…”
Section: Discussionsupporting
confidence: 92%
“…a The tobacco root transformed with plasmid pBI121; b The tobacco root transformed with plasmid p1200::GUS; c The tobacco root transformed with plasmid p900::GUS; d The tobacco root transformed with plasmid p600::GUS; e The tobacco root transformed with plasmid p400::GUS; f The tobacco root transformed with plasmid pBI101; g The wild tobacco root showed that the upstream of the promoter sequence contained many core elements such as TATA-box (− 30 bp) and CAAT-box (− 96 bp), and the distance from TATA-box or CAAT-box to TSS was consistent with that of the results described in the previous studies in other plant promoters [29]. Besides the core components TATA-box and CAAT-box, the EcGS1b-P also had rootspecific function motif and cis-acting elements that were regulated by light, heat, hormones and temperature, which was also consistent with the previous studies [54][55][56][57]. It is worth to note that GS1b promoter contained root-specific expression element ROOT-MOTIFTAPOX, which indicated EcGS1b might be a root-preferential expression gene.…”
Section: Discussionsupporting
confidence: 92%
“…Heat induces the splicing of bZIP60 by IRE1 (inositol-requiring enzyme 1); IRE1 confers heat stress tolerance, and this is attributable to its RNase domain [51,52] bZIP60, HSFTF13, HSPs Maize Maize heat stress response; bZIP60 links the UPR (unfolded protein response) to the HSR in maize by direct binding bZIP60 to the promoter of Hsftf13 to active its expression [14] bZIP60 Maize bZIP60 expression levels in tropical and temperate maize lines with different heat tolerances [53] Others transcriptional processes ABA/ calcium/ SA/ethylene, etc.…”
Section: Heat Stress Response (Hsr) a Cytoplasmic Heat Stress Responsementioning
confidence: 99%
“…Heat, salt, drought, extreme osmotic and heavy metals stresses can activate the UPR in plant cell ( Gao et al., 2008 ; Deng et al., 2011 ; Liu et al., 2011 ; Wang et al., 2011 ; Zhang et al., 2017 ; Li et al., 2018 ). There are also some reports linking pathogen attack and the activation of UPR ( Tateda et al., 2008 ; Moreno et al., 2012 ; Ye et al., 2012 ; Sun et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%